Analisis Penilaian Kinerja Pegawai Pada Bagian Kepegawaian dan Umum Direktorat Jenderal P2P Kementerian Kesehatan - Chusminah Chusminah; R Ati Haryati (Widya Cipta - Jurnal Sekretari dan Manajemen, 2019)
Managing human resources is one of the important elements in any company organization or institute activities. On scope of human resources management there are various human resources activities were an act of taken to provide and maintaining performance adequate for the organization. Through performance assessment be used as a stage of work evaluation that can enhance the quality of employees and produces accurate information behavior and performance of members of the organization. This final project is a qualitative descriptive study with method of observation, interviews, and method of documentation. Implementation of performance assessment at Human Resources and General Affair conducted at the end of the year with calculate the element of SKP and work behavior as well as two additional elements, additional duties and creativity. Based on the result of research concerning the performance assessment results period of January-December 2017, for the highest SKP performance assessment is 96 and the lowest is 83 and the highest assessment of work behavior 90 and the lowest 76, the highest average value is 89.84. The method used in performance assessment is rating scale. Keywords: Performance Appraisal